2021
DOI: 10.1101/2021.05.16.444345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distance-guided protein folding based on generalized descent direction

Abstract: Advances in the prediction of the inter-residue distance for a protein sequence have increased the accuracy to predict the correct folds of proteins with distance information. Here, we propose a distance-guided protein folding algorithm based on generalized descent direction, named GDDfold, which achieves effective structural perturbation and potential minimization in two stages. In the global stage, random-based direction is designed using evolutionary knowledge, which guides conformation population to cross … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…First, the master structure database is constructed by using MMseqs2 [23,24], HHsuite [25], and DSSP [26,27] on the basis of the latest Protein Data Bank (PDB, 2021-08). Then, the HMM-profile of query sequence is constructed and chopped into a nested set of segments (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) including the clustering of sequences in PDB, the generation of the HMM-profile, and the calculation of secondary structure distribution. The generation of the variable-length fragment library is shown by the orange arrow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the master structure database is constructed by using MMseqs2 [23,24], HHsuite [25], and DSSP [26,27] on the basis of the latest Protein Data Bank (PDB, 2021-08). Then, the HMM-profile of query sequence is constructed and chopped into a nested set of segments (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) including the clustering of sequences in PDB, the generation of the HMM-profile, and the calculation of secondary structure distribution. The generation of the variable-length fragment library is shown by the orange arrow.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of the variable-length fragment library is shown by the orange arrow. First, the HMM-profile of the query sequence is generated by HHsuite and chopped into a nested set of segments (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Then, the fragments are obtained by profile-profile comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins are essential to life, and predicting their structures from sequences can facilitate the understanding of their functions. Various methods have been proposed to predict the three-dimensional structure of proteins [1-6]. The successful application of deep learning in recent years has significantly improved the accuracy of structure prediction [7-14], especially the end-to-end deep learning methods AlphaFold2 [15], whose prediction accuracy on most of the Critical Assessment of techniques for protein Structure Prediction (CASP14) targets is close to experimental results [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that fragments are essential for fragment assembly-based methods. However, current fragment libraries remain inadequate, and the accuracy of prediction models generated by fragment assembly will be difficult to reach expectations when fragment libraries lack fragments with near-native fragment structures [21, 22]. Designing a variable-length fragment library with increased completeness is crucial for improving the accuracy of prediction models.…”
Section: Introductionmentioning
confidence: 99%